1991
DOI: 10.1172/jci115475
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of hyaluronan and tissue edema in experimental myocardial infarction.

Abstract: Experimental myocardial infarction was induced in rats. The myocardial accumulation of hyaluronan (HA) and water during the development of infarction was measured. The extractable HA content of the infarcted area increased progressively from day 1 and on day 3 reached a threefold increase compared with the HA amounts in myocardium of sham operated controls. The relative water content of infarcted areas also increased progressively reaching a maximum value by day 3 and was strongly correlated with the HA accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 25 publications
(17 reference statements)
2
31
0
Order By: Relevance
“…It was the first GAG discovered in 1934 by Karl Meyer and John W. Palmer 37 and, therefore, most comprehensively described in the heart. [38][39][40][41][42][43][44][45][46][47][48][49][50] The expression of hyaluronan is upregulated in experimental models of myocardial infarction (MI), 50 myocarditis, 51 and cardiac hypertrophy. 43,49 In 1985, West et al 52 demonstrated that oligosaccharides derived from high-molecular-weight hyaluronan can have very distinct functions compared with the large hyaluronan variants.…”
Section: Hyaluronan and Heparinmentioning
confidence: 99%
“…It was the first GAG discovered in 1934 by Karl Meyer and John W. Palmer 37 and, therefore, most comprehensively described in the heart. [38][39][40][41][42][43][44][45][46][47][48][49][50] The expression of hyaluronan is upregulated in experimental models of myocardial infarction (MI), 50 myocarditis, 51 and cardiac hypertrophy. 43,49 In 1985, West et al 52 demonstrated that oligosaccharides derived from high-molecular-weight hyaluronan can have very distinct functions compared with the large hyaluronan variants.…”
Section: Hyaluronan and Heparinmentioning
confidence: 99%
“…As in any other ischaemic condition an early feature is an unspecific inflammatory reaction in the border zone that surrounds irreversibly damaged tissue, recognized in the form of an interstitial oedema and infiltration of inflammatory cells. We assumed that this inflammatory reaction, although unspecific in its nature, affected the interstitial HYA concentration we evaluated this hypothesis in rats by ligation of the descending branch of the left coronary artery [35], which causes a predictable anterior wall infarction. The HYA content of the infarcted area increased progressively from day 1 and at day 3 reached a maximum that was threefold that of sham operated controls.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Hyaluronan (HA),' a component of the extracellular matrix, has been implicated in cell locomotion during embryogenesis (8,9), tumor invasion (10), transformation by oncogenes ( 11), and in responses to injury (12)(13)(14). HA has also been shown to stimulate the migration of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%